A house of rage and sorrow - Mandanna, Sangu (Mandanna, Sangu. Celestial trilogy, 2019)
"Seeking a powerful weapon to avenge her broken heart, Esmae tackles threatening elements of her past and an army of supernatural enemies while searching for the truth behind what happened to her father." --